On the reducibility of linear differential operators with unbounded operator coefficients - Baskakov, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The general solutions of linear boundary-value problems for systems of ordinary differential equations under pulse influence are constructed by using semireciprocal matrices and the generalized Green matrix.